Supply Chain Management dan Rencana Pelayaran Nasional PT Pelni Terhadap Disparitas Harga di Indonesia Bagian Timur - Asep Suparman; Muhammad Fadli Heryadi; Dedeng Wahyu Edi (Institut Transportasi dan Logistik Trisakti, 2019)
PT. Pelayaran Nasional Indonesia (PT. Pelni) is a company engaged in inter-island crossing transportation service providers. The purpose of the study is to find out and analyze the influence of supply chain management and national shipping company (PT. Pelni) plan in suppressing the East Indonesia price disparity in 2016. To solve the problem of the research, the researchers used 2 methods: field research and library data for collecting data. Both methods of data analysis are processed using multiple regression analysis, with validity test, reliability test, t test, F test, and coefficient of determination. The results of the analysis and discussion show a fairly high influence between supply chain management and the national shipping plan on the price disparity of goods needed as indicated by the multiple linear regression line equation namely: Y = 14,947 + 0,318 X1 + 0,064 X2. Based on the results of the F test, where the variables X1 and X2 give effect to the Y variable together, then the results of the analysis, F count is 3,807. Then, F count > F table which is 3.807 > 3.35 proves that Ho is rejected and Ha is accepted. Therefore, there is a strong and positive multiple relation between supply chain management performance variable and the national shipping plan variable towards the price disparity variable with coefficient determination of 22%.